2020
DOI: 10.14444/7008
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Tomography–Based Morphometric Analysis of Odontoid in 100 Egyptian Patients

Abstract: Background: There is still no consensus in the literature regarding the use of 1 screw or 2 screws. A number of studies have proved ethnic variations in the morphometry of the odontoid. There is no literature on the morphometry of odontoid in Egyptian patients. Methods: Computerized tomography (CT) scans of the head and cervical spine of 100 healthy (no evidence of cervical spine fracture) patients of Egyptian origin were studied. Measurements were performed using Horos software, which allowed exact morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was detected in 24 male (24/39) and 15 female (15/39) patients and Type II was recorded in 73 cases (65.2%). It was depicted in 44 male (44/73) and 29 female (29/73) patients and a higher prevalence in the ≤30y age group were pyramidal while the oval type showed a higher prevalence in the >30 age group (statistically significant differences) (23)(24)(25)(26)(27) . Regarding the morphological variants of the dens: In the present study we found one variant (persistent ossiculumterminale) among the sample in contrast to Perdikakis et al (2012) in their study on a Greek population retrospectively reviewing 112 patients who found an osterminale could be identifiable (with different degrees of ossification and fusion) in 22 cases (22-26-27) .…”
Section: Sharma Et Al(2008)mentioning
confidence: 99%
“…It was detected in 24 male (24/39) and 15 female (15/39) patients and Type II was recorded in 73 cases (65.2%). It was depicted in 44 male (44/73) and 29 female (29/73) patients and a higher prevalence in the ≤30y age group were pyramidal while the oval type showed a higher prevalence in the >30 age group (statistically significant differences) (23)(24)(25)(26)(27) . Regarding the morphological variants of the dens: In the present study we found one variant (persistent ossiculumterminale) among the sample in contrast to Perdikakis et al (2012) in their study on a Greek population retrospectively reviewing 112 patients who found an osterminale could be identifiable (with different degrees of ossification and fusion) in 22 cases (22-26-27) .…”
Section: Sharma Et Al(2008)mentioning
confidence: 99%